Technology and Film Scholarship: Experience, Study, Theory - Hidalgo, Santiago; Gaudreault, André (Film Theory in Media History, 2017)
This volume brings together a wide range of explorations of the ways in which technological innovations have established new and changing conditions for the experience and study of film. The book offers analyses by such leading figures in film studies as Tom Gunning and Charles Musser, who examine the ways in which technological changes have altered the ways how cinema is conceived and how it is approached as an object of study. Contributors also look at the overlapping stages through which new experience is translated in institutionalized knowledge within the discipline.